Proceso de atención de enfermería en neonato de 40 horas de vida con sepsis neonatal. - Luque Pesantes, Korayma Lilibeth (2020)
The purpose of this clinical case in to provide the nursing care process in a 40 hours old newborn patient with a diagnosis of sepsis, the reason why sepsis was caused in the aforementioned patient was due to intra-amniotic infection dur calving. Neonatal sepsis is an invasive infection, caused by bacteria, fungi or virus in the blood, it manifests within the firs 28 hours of life, through blood culture the infection is evaluated in the patient in case the result is negative, it is considered clinical sepsis, it is important to identify the microorganism causing the sepsis in order to establish the appropriate treatment with antibiotics. Sepsis is classified according to its onset, if it occurs in the first 72 hours of life it is considered early onset sepsis and if it appears after 72 hours of life it in considered late onset or nosocomial sepsis, for that, it is important to know the risk factors present in the patient. It is here, where an important role is occupied through the correct collection of data for its adequate evaluation through the physical examination, which leads to a correct diagnosis of nursing.